Các cơ chế chuẩn đoán virus tin học thông minh dựa trên tri thức - Thủy, Nguyễn Thanh; Quang, Trương Minh Nhật (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall investigate a knowledge-based diagnostic mechanism in an intelligent antivirus system. Ali overall system structure will be presented. The first difficult task in the diagnostic Processing is the feature extraction. We proposed some basic behavious of B-viruses and F-viruses. Then, based on these caracteristics, a careful statistics for 100 typical F-viruses and 60 B-viruses is carried out. The obtained results helped us to create a konwledge base in the form of the production rules. Two different inferent mechanisms over knowledge base are discussed. Another contribution, in this paper is a proposition of binary representation of an executable program E. Some experimentation of the Interlligent Antivirus system are studied based on a Virtual machine.